Skeletal muscle satellite cells are located at a closer proximity to capillaries in healthy young compared with older men. Issue 5 (15th February 2016) - Nederveen, Joshua P; Joanisse, Sophie; Snijders, Tim; Ivankovic, Victoria; Baker, Steven K.; Phillips, Stuart M.; Parise, Gianni
Abstract: Background: Skeletal muscle satellite cells (SC) are instrumental in maintenance of muscle fibres, the adaptive responses to exercise, and there is an age‐related decline in SC. A spatial relationship exists between SC and muscle fibre capillaries. In the present study, we aimed to investigate whether chronologic age has an impact on the spatial relationship between SC and muscle fibre capillaries. Secondly, we determined whether this spatial relationship changes in response to a single session of resistance exercise. Methods: Muscle biopsies were obtained from the vastus lateralis of previously untrained young men (YM, 24 ± 3 years; n = 23) and older men (OM, 67 ± 4 years; n = 22) at rest. A subset of YM ( n = 9) performed a single bout of resistance exercise, where additional muscle biopsies taken at 24 and 72 h post‐exercise recovery. Skeletal muscle fibre capillarization, SC content, and activation status were assessed using immunofluorescent microscopy of muscle cross sections. Results: Type II muscle fibre SC and capillary content was significantly lower in the YM compared with OM ( P < 0.05). Furthermore, type II muscle fibre SC were located at a greater distance from the nearest capillary in OM compared with YM (21.6 ± 1.3 vs. 17.0 ± 0.8 µm, respectively; P < 0.05). In response to a single bout of exercise, we observed a significant increase in SC number and activation status ( P < 0.05). In addition, activated vs. quiescent SC were situated closer ( P < 0.05) to capillaries. Conclusions: We demonstrate that there is a greater distance between capillaries and type II fibre‐associated SC in OM as compared with YM. Furthermore, quiescent SC are located significantly further away from capillaries than active SC after single bout of exercise. Our data have implications for how muscle adapts to exercise and how aging may affect such adaptations.